Variationsrechnung: 18.6. bis 24.6.1972 - Heinz, Erhard; Hildebrandt, Stefan; Jäger, Willi (Tagungsbericht, 1972)
W. K. Allard, Pisa; F. J. Almgren, Princeton; H. W. Alt, Münster; W. Alt, Münster; L. Cesari, Ann Arbor; M. Emmer, Ferrara; I. Frehse, Heidelberg; C. Gerhardt, Mainz; K. Goldhorn, Mainz; K. Gornik, Bonn; J. Guckenheimer, Princeton; R. Gulliver, Berkeley; F. P. Harth, Bonn; E. Hölder, Mainz; H. Kaul, Bonn; F. Lewerenz, Göttingen; R. Meise, Mainz; M. Miranda, Ferrara; J. C. C. Nitsche, Minneapolis; H. Pecher, Göttingen; B. Schmidt, Bonn; H. Schmidt, Münster; U. Staude, Mainz; K. Steffen, Bonn; F. Tomi, Münster; W. von Wahl, Bonn